New multivariate prognostic model for predicting early lethal outcome after acute period of spontaneous supratentorial intracerebral hemorrhage with secondary intraventricular hemorrhage - Kuznietsov, A. A.; Kozyolkin, O.; Кузнєцов, Антон Анатолійович; Козьолкін, Олександр Анатолійович (John Wiley & Sons, Ltd., 2017)
Background and aims: Identification of vital prognosis in patients with acute spontaneous supratentorial intracerebral hemorrhage (ASSICH) with secondary intraventricular hemorrhage (SIVH) is a very important and relevant in modern angioneurology that can help the practicioners to improve treatment approaches. Therefore the aim was elaboration of new multivariate statistical for predicting ELO after ASSICH with SIVH using clinical and paraclinical parameters. Background and aims: Identification of vital prognosis in patients with acute spontaneous supratentorial intracerebral hemorrhage (ASSICH) with secondary intraventricular hemorrhage (SIVH) is a very important and relevant in modern angioneurology that can help the practicioners to improve treatment approaches. Therefore the aim was elaboration of new multivariate statistical for predicting ELO after ASSICH with SIVH using clinical and paraclinical parameters. Background and aims: Identification of vital prognosis in patients with acute spontaneous supratentorial intracerebral hemorrhage (ASSICH) with secondary intraventricular hemorrhage (SIVH) is a very important and relevant in modern angioneurology that can help the practicioners to improve treatment approaches. Therefore the aim was elaboration of new multivariate statistical for predicting ELO after ASSICH with SIVH using clinical and paraclinical parameters.